Police civil liability: An analysis of section 1983 actions in the Eastern and Southern districts of New York - Chiabi, David K. (American journal of criminal justice, 1996)
This article examines the Section 1983 civil damage remedy and the Bivens-type action — the direct claim of the victim of official wrongdoing to obtain compensation for the denial of his or her Fourth Amendment rights. Using court records of cases filed under this statute from 1983 to 1987 in the Eastern and Southern districts of New York, the study determined: (1) the nature and volume of damages awarded by the courts in Section 1983/Bivens actions, (2) the differences in the amount of damages recovered from bench trials, jury trials, and settlements, (3) the parties involved in Section 1983 suits, (4) the trials and settlements, and (5) the time and resources spent by the parties and the courts on these cases. The analysis of the data was used to gauge the impact of these suits on individual police and police administrators.